Possible Ways of Regulating Labour Protection of Economically Dependent Self-Employed Workers - Moras-Olaś, Kinga (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The necessity to cover economically dependent self-employed persons, i.e. a group of people providing work as part of their economic activity, based on contracts that do not lead to an employment relationship, but in conditions similar to employees, with labour protection regulations should not raise doubts, in particular in the context of Art. 24 of the Polish Constitution. The article aims to briefly present the possible ways of regulating this subject matter, in particular from the system perspective, and to present the approach that is, in the author’s opinion, the optimal one. Proposals in this respect include various concepts of protecting economically dependent self-employed workers, ranging from maintaining the status quo to including economically dependent self-employment in the scope of the employment relationship. However, none of these extreme concepts seems to be correct and it is necessary to look for a golden mean. It seems most desirable to distinguish the self-employment in question as a separate legal category in conjunction with the granting of certain rights to members of this group. Adopting this direction will allow for the delimitation of economically dependent self-employment and the employment relationship connected with providing the required protection to entities providing work in this form, adapted to its specificity.